A New Approach to Semantic Parsing of Metonymic Phrases by a Business Intelligence System - Fomichov, Vladimir A. (2023 46th MIPRO ICT and Electronics Convention (MIPRO), 2023)
The functioning of numerous business intelligence systems (BIS) substantially depends of the content of databases. In many thematic domains, this content is highly dynamic, e.g., in case of the prices for oil, aluminum, wheat, etc. It is the reason for the birth of a BIS project aimed at updating the content of relational databases by means of extracting actual values of data from the texts in natural language (NL). The principal subject of the paper is theoretical foundations of building semantic representations (SRs) of the metonymic phrases. In linguistics, a metonymic construction is a linguistic construction in which an entity is referred to by the name of something closely associated with that thing or situation. The main scientific results set forth in the paper are as follows: (a) a logical structure of a minimalist terminological knowledge base helping to fulfil semantic parsing of metonymical phrases, it is motivated by the theory of K-representations; (b) an original algorithm of finding a semantic interpretation of metonymic phrases of some kinds.